ANALISIS TENTANG TIPE BUDAYA POLITIK MAHASISWA UNIVERSITAS RIAU - Rindi Septia Dewi; Sri Erlinda; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is in background with the role of the student begins to fade. This happens because of the culture of modernization and globalization that tends to erode the idealism and awareness of the nation and state. Not only at the national level even at the lowest levels of student awareness which has begun to be questioned. The students tend to be apathetic to issues that occur in the community. The formulation of this research problems were whether of the type of political culture of the students of Universitas Riau and what factors that affect the political culture of the students of Universtias Riau?. The aims of this research is to determine the political culture of the students of Universitas Riau and what factors that affect the political culture of the students of Universitas Riau. Based on the research findings of this research can be concluded that the percentage of respondents' recapitulation of answers questionnaire about the analysis of the type of political culture of the students of Universitas Riau which is answers on the type of parochial political culture that "Agree" 0%, "69,44" Politics of participants who "Agree" as much as 30.92%, of the three types of political culture and political culture of university students riau is a subject political culture. There were some factors that affect the political culture of the highest representation that responds "Agree" are at the educational level, 96.8. While factors that influence the political culture of the highest participants who answered "Agree" is in the level of education 96.36%. Baseded on the interviews that the respondents revealed that the low political culture of student participants to the world of politics is due to the fact that students are less concerned about political activities and are busy with their solid schedules in academic and personal affairs.Keywords: Type of political culture, Student